Investigating the major factors that contribute to satisfaction with university formation in Psychology and Teaching in Chile. Issue 1 (2nd January 2022) - Espinoza, Oscar; González, Luis Eduardo; Sandoval, Luis; Loyola, Javier; McGinn, Noel; Castillo, Dante
ABSTRACT: The objective of this study was to understand which factors contribute most to Psychology and Teaching graduates' satisfaction with their university professional formation. Two factors were assessed: the level of admissions selectivity by the university attended, and the salary received once employed. The participants graduated from three universities in Chile, one public and two private selected as representing three levels of university selectivity. The sample was constructed by random selection among five cohorts of graduates, from 2012 to 2016. A self-report questionnaire was administered on two occasions, in 2015 for the first three cohorts and in 2017 for the last two. The obtained sample included 587 graduates, in Psychology and in Teaching of Basic Education. The results reveal that selectivity is related to graduates' satisfaction with their university experience; the more selective the university in which they are admitted, the more graduates are satisfied. Salary, on the other hand, is related to satisfaction only in the case of the least selective university. The findings provide some directions for how universities can improve graduates' satisfaction.